Dampak Penggunaan Gadget Terhadap Perkembangan Sosial Emosional Anak Usia 2-5 Tahun - Nazala Aima (Indonesian Journal of Elementary and Childhood Education, 2024)
In line with the rapid advancement of technology, the use of devices, especially smartphones, among young children is increasing. This study aims to examine the effects of device use on the social-emotional development of children aged 2-6 years in South Gelogor Village, West Lombok Regency. The method used in the study was descriptive qualitative by conducting observations and interviews with 9 respondents, consisting of 5 children and 4 parents. The results indicate that the use of the device has positive effects such as making it easier for parents to deal with fussy children and improving children's language skills through educational viewing. However, negative effects include device addiction, reduced social interaction, and increased tantrum behavior. Parents have an important role in controlling the use of devices, by limiting time and supervising, to maximize the positive effects and minimize the negative effects. This study recommends the need for close supervision of children's device use, as well as the importance of selecting appropriate content to support optimal social-emotional development.